1995
DOI: 10.3354/meps129041
|View full text |Cite
|
Sign up to set email alerts
|

Respiration rate of adult pilchard Sardinops sagax in relation to temperature, voluntary swimming speed and feeding behaviour

Abstract: Laboratory experiments investigated the effect of temperature, voluntary swimming speed and feeding behaviour on the respiration rate of adult pilchard Sardinops sagax. Mean routine respiration was 0.178 i 0.055 mg O2 g-' wet wt h-' Respiration rate increased exponentially with temperature, and the mean QIo over the temperature range 10 to 22OC was 1.82 * 0.35. Significant linear relationships were established between respiration rate and voluntary swimming speed for non-feeding, filter-feeding and particulate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
19
0

Year Published

1998
1998
2020
2020

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 43 publications
(22 citation statements)
references
References 25 publications
(43 reference statements)
3
19
0
Order By: Relevance
“…The low variance associated with the O t h e r c r u s t a c e a n s C r u s t a c e a n e g g s C r u s t a c e a n n a u p l i i mean frequency of occurrence values for the small size-classes indicated that such prey were common in all stomach content samples, and therefore were consistently ingested by sardine. These results corroborate previous experimental (van der Lingen 1994(van der Lingen , 1995 and field studies (Davies 1957, Hand and Berner 1959, King and Macleod 1976, Alamo and Bouchon 1987, van der Lingen 1998b, which suggest that sardine are predominantly filter-feeders. Sardine stomach contents appear to reflect both the size frequency distribution and the prey composition of the ambient plankton community as sampled by the Magnum rosette, although the Magnum rosette is not a comprehensive sampler of the food environment.…”
Section: Discussionsupporting
confidence: 91%
“…The low variance associated with the O t h e r c r u s t a c e a n s C r u s t a c e a n e g g s C r u s t a c e a n n a u p l i i mean frequency of occurrence values for the small size-classes indicated that such prey were common in all stomach content samples, and therefore were consistently ingested by sardine. These results corroborate previous experimental (van der Lingen 1994(van der Lingen , 1995 and field studies (Davies 1957, Hand and Berner 1959, King and Macleod 1976, Alamo and Bouchon 1987, van der Lingen 1998b, which suggest that sardine are predominantly filter-feeders. Sardine stomach contents appear to reflect both the size frequency distribution and the prey composition of the ambient plankton community as sampled by the Magnum rosette, although the Magnum rosette is not a comprehensive sampler of the food environment.…”
Section: Discussionsupporting
confidence: 91%
“…Most knowledge on the life history and behaviour of these small clupeoids is obtained indirectly from the analysis of long series of biological data from catch samples (Parrish et al , 1986; Silva et al , 2006) or from survey observations (Freon & Misund, 1999). In a few cases, successful maintenance of such species in captivity has provided valuable information on feeding behaviour (van der Lingen, 1994; Garrido et al , 2007), reproduction (Olmedo et al , 1990; Matsuyama et al , 1991; Shiraishi et al , 1996) and bioenergetics (van der Lingen, 1995). Schooling small pelagic fishes, however, are sensitive to capture and handling (Stratoudakis et al , 2003; Marçalo et al , 2006), since escape reactions within the crowded nets can cause extensive scale loss and abrasions that lead to bacterial infections and high mortality rates (James et al , 1988; Mitchell et al , 2002).…”
Section: Introductionmentioning
confidence: 99%
“…Sardine is predominantly a filter-feeding species which is able to capture food particles down to 17 pm in size (van der Lingen 1994), and which maximizes its energy gain through prolonged bouts of energetically cheap filtering (van der Lingen 1995). Sardine stomachs typically contain both phytoplankton and zooplankton prey (Davies 1957, King & Macleod 1976, van der Lingen 1996, and the minimal die1 variation in stoinach content mass suggests that these fish filterfeed almost continuously (van der Lingen 1998).…”
Section: Introductionmentioning
confidence: 99%